Analysis of innovation management in German enterprises - Alireza Nasiri (Taylor & Francis Group, 2016)
In the drive towards economic globalization, companies are faced with both opportunities and challenges. As the global landscape changes, company and by extension countries increasingly grasp the level of importance innovation has to their survival and continued development. The element of innovation, within the business environment, has become the necessary condition for sustainable development of a country or nation. In the case of Germany, the authors acknowledge the country’s fascinating ability in innovation management; therefore have sought to gain a better understanding through a sampled analysis of German private enterprises. In the process, quantitative model and qualitative model were utilized together. On the one hand, a qualitative method is adopted to collect primary data. On the other hand, a quantitative process is used to collect secondary data. According to the data analysis of the sampled corporations and businesses, the indices of each factor vary across the different industries. Results also suggested that stronger enterprises give greater attention to innovation (factors) and therefore reap higher gains. In such companies, various rules and regulations are designed to stimulate the employees’ creativity; while communication is established across all parts of companies. Similarly, the company would be design on the basis of adapting different market strategies. Worthy of note is that companies in each industry treat technological innovation as an important element to their development. Such emphasis on the importance of innovation management is a vital factor that can aid in explaining why German enterprises have gained such success to date. Hence, companies in other world economies, including fast pace China should take note of the German companies and strengthen their own management structure regarding innovation.